2019
DOI: 10.1177/0306624x19849565
|View full text |Cite
|
Sign up to set email alerts
|

Examining Developmental Patterns of Prison Misconduct: An Integrated Model Approach

Abstract: Recent prison scholarship has employed an integrated model of the developmental/life-course perspectives and importation model to examine prison misconduct. Using longitudinal data from a large sample of inmates incarcerated in a U.S. prison system, this study attempts to validate and expand recent prison research by systematically examining the relationship among inmate characteristics and misconduct trajectories, particularly for the higher/chronic pattern of misconduct relative to other identified clusters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The findings of this study can be summarized as follows: the most frequent misconduct perpetrators as juvenile wards—the top 10% misconduct perpetrators while in juvenile confinement—were predicted to engage in a higher expected rate of violent misconduct in the adult prison setting. This finding is in line with prior research (Cihan & Sorensen, 2019; Craig & Trulson, 2019). Second, the youngest offenders with respect to the age that they were initially committed to the adult prison system were predicted to engage in higher levels of violent misconduct, net the effects of other variables in the model, which is consistent with prior research (Steiner et al, 2014; Trulson et al, 2016; Valentine et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of this study can be summarized as follows: the most frequent misconduct perpetrators as juvenile wards—the top 10% misconduct perpetrators while in juvenile confinement—were predicted to engage in a higher expected rate of violent misconduct in the adult prison setting. This finding is in line with prior research (Cihan & Sorensen, 2019; Craig & Trulson, 2019). Second, the youngest offenders with respect to the age that they were initially committed to the adult prison system were predicted to engage in higher levels of violent misconduct, net the effects of other variables in the model, which is consistent with prior research (Steiner et al, 2014; Trulson et al, 2016; Valentine et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…In the decades since the development of importation theory, numerous studies provided empirical support for the notion that pre-prison behavioral risk factors including criminal history, prison history, gang involvement, and externalizing psychopathology were associated with greater institutional maladjustment and misconduct (e.g., Cao et al, 1997; Choi & Dulisse, 2020; Cihan & Sorensen, 2019; DeLisi & Butler, 2020; Hochstetler & DeLisi, 2005; Lai, 2019; Walters & Crawford, 2013). In recent years, the importation model has undergone modification to more explicitly recognize life-course developmental periods that occur both prior to confinement and after release from custody.…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, their study did not contain any prison homicide data. Still other research found that current homicide conviction was associated with having low misconduct while in prison (Cihan & Sorensen, 2019). Cunningham et al (2010) examined 35 inmate murders occurring in Texas prisons from 2000 to 2008.…”
Section: Homicide As An Importation Factormentioning
confidence: 99%
“…Generally, these studies indicate that determinants of prison misconduct and violence are similar to those "that have traditionally provided insight into postrelease recidivism" [(19); p. 710]. Hence, recent life course/developmental perspectives suggest that prison misconduct may rather represent a continuation of a pattern of delinquency (20)(21)(22) than an interruption (23). It was emphasized that studying prison behavior can further improve the understanding of recidivism (20).…”
Section: Prison Behavior: Empirical Evidence and Conceptual Consideramentioning
confidence: 95%